IDENTIFIKASI DAN PENGEMBANGAN PROGRAM INTERNALISASI NILAI CHARITY DI PERGURUAN TINGGI X - Murwanto; DOMINIKUS BUDIARTO BUDIARTO (Jurnal Keuangan dan Bisnis, 2019)
Value is highyly needed in an organization, and in a “status quo” situation, for taking decision and facing a complex problems.University X (PT) is a result of merging of three Colleges (Sekolah Tinggi). That are Engineering college (STT), Economic Science College (STIE), and Health Science College (STIKES). As a University, those three colleges change into faculties, that are Faculty of Science and Technolog (FST), Faculty of Business and Accounting (FBA), and Faculty of Health Science (FIKES) Charity value is equality profile of human resources tha aim to be developed. The problem is the value internalization level still remains unknown, and also planning that is able to the value to be organization culture so it is seen in individual attitude of academic community. The research aims to (1) Evaluate the implementation/internalization of Charity value at PT X. (2) Indentify factors that cause internalization of charity value that is less optimal.(3) Design strategy in order to optimize the proces of internalizing charity value. Generally the problems solving process follows these steps: (1) Formulate the problem. The identification result showed that there was 29% GAP in Charity value. (2) Analyze the problem. Some factors that become main problem in intenarlizing the Charity values are individual character, knowlegde, skill, and previous organization culture (3) Search for alternative solutions. Selected program of specification design to minimize the present GAP, that are teaching-learning activities (KBM), Team Building/Refreshing, Training/Course, Seminar/Workshop/Converence, Mentoring, and Students’ organization ctivities. (4) Decide among the alternative and Specify the solution. The chosen program result is teaching-learning activities.